Determinants of Risk Management Disclosure Study of Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange - Yolifiandri, Yolifiandri; Kamil, Islamiah; Anjarwati, Sri (Journal of Accounting and Finance Management, 2024)
This research aims to analyze how risk management disclosure is seen from the implementation of corporate governance (institutional ownership, audit committee, independent commissioner) and company size, which is the main issue of this article, which business actors hope can mitigate business risks. The population of this research is banking industry companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The research sampling technique that the researcher used was purposive sampling. The analysis technique that researchers use is multiple regression analysis and descriptive statistics. The data analysis that researchers used was with the help of the SPSS version 26 application. The results of this research simultaneously show that company size, audit committee, independent commissioner and institutional ownership jointly influence risk management disclosure. Partially, company size has an effect and is not significant on risk management disclosure, the audit committee has a significant effect on risk management disclosure. independent commissioners have an inversely proportional effect on risk management disclosures, there is an influence of institutional ownership which is not significant and inversely proportional to risk management disclosures